2020
DOI: 10.1186/s12904-020-00575-4
|View full text |Cite
|
Sign up to set email alerts
|

End-of-life care in a pediatric intensive care unit: the impact of the development of a palliative care unit

Abstract: Background: The purpose of this paper is to describe how end-of-life care is managed when life-support limitation is decided in a Pediatric Intensive Care Unit and to analyze the influence of the further development of the Palliative Care Unit. Methods: A 15-year retrospective study of children who died after life-support limitation was initiated in a pediatric intensive care unit. Patients were divided into two groups, pre-and post-palliative care unit development. Epidemiological and clinical data, the decis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 38 publications
(43 reference statements)
2
20
0
6
Order By: Relevance
“…As highlighted previously, we found that PICU deaths accounted for most deaths within our tertiary care pediatric hospital ( 14 ). A previous study in a Japanese PICU reported the mortality rate to be ~3.3%, which was consistent with that reported in our study (3.6%).…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…As highlighted previously, we found that PICU deaths accounted for most deaths within our tertiary care pediatric hospital ( 14 ). A previous study in a Japanese PICU reported the mortality rate to be ~3.3%, which was consistent with that reported in our study (3.6%).…”
Section: Discussionsupporting
confidence: 71%
“…Since the 1990s, WLST practices have been well-defined in literature ( 14 , 23 ). We examined WLST status at death based on medical records.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations